Effects of a semi-synthetic N-,O-sulfated glycosaminoglycan K5 polysaccharide derivative in a rat model of cerebral ischaemia/ reperfusion injury - Collino, Massimo; Castiglia, Sara; Manoni, Marco; Salsini, Liana; Chini, Jacopo; Masini, Emanuela; Fantozzi, Roberto (Thrombosis and Haemostasis, 2009)
Heparin and low molecular weight heparins may reduce brain damage evoked by ischaemia/reperfusion (I/R) injury, although their use is hampered by the risk of haemorrhage. Chemical and enzymatic modifications of K5 polysaccharide have shown the possibility to produce heparin-like compounds with low anticoagulant activity and strong anti-inflammatory effects. Using a rat model of transient cerebral I/R, we investigated the effects of an epimerised N-,O-sulfated K5 polysaccharide derivative, K5-N,OSepi, on the infarct size, motor activity and injury caused by ischaemia (30 min) and reperfusion. Reperfusion was allowed for 60 min or 1–5 days. Rats reperfused for 5 days showed an infarct volume of 30.7 ±3.1% and K5-N,OSepi (0.1–1 mg/kg) caused dose-dependent reduction in infarct size (maximum at 1 mg/kg: 13.1 ±2.1% infarct volume). This effect was associated with a significant improvement in motor performance. In the rat hippocampus, one of the brain areas most sensitive to I/R injury, I/R induced a robust increase in myeloperoxidase (MPO) activity, a marker of neutrophil infiltration, that was halved by K5-N,OSepi administration (66.38 ±7.75 µU MPO/tissue g, 30.78 ±5.67 µU MPO/tissue g, respectively). K5-N,OSepi drastically reduced the expression of cyclooxygenase-2,inducible-nitric-oxide-synthase and intercellular-adhesion-molecule-1. I/R-induced activation of nuclear factor-kB was attenuated by drug treatment. Furthermore, K5-N,OSepi administration was associated with a significant modulation of apoptosis markers, such as Bid and Bcl-2. In conclusion, the results demonstrated that the sulfated semi-synthetic K5 derivative K5-N,OSepi protects the brain against I/R injury by disrupting multiple levels of the apoptotic and inflammatory cascade, including inhibition of NF-κB activation.
Keywords: Heparin-like derivative; hippocampus; cerebral ischaemia/reperfusion; inflammation